Multimodal Approaches in Science Teacher Education: An Integrative Review of Technologies, Representations, and Pedagogical Models - Gunawan Gunawan; Kosim Kosim; Baiq Nabila Saufika Zainuri; Qothrunnada Qothrunnada (Indonesian Journal of Teacher Education, 2025)
Modern science education increasingly demands the integration of diverse instructional modes to foster deep conceptual understanding and higher-order thinking skills. This integrative review examines the implementation of multimodal approaches within science teacher education, focusing on the synergy between digital technologies, multiple representations, and student-centered pedagogical models. By synthesizing recent literature, this study explores how tools such as virtual laboratories, interactive multimedia, and PhET simulations are utilized alongside Problem-Based Learning (PBL) and inquiry-based frameworks to enhance pre-service and in-service teachers' competencies. The analysis reveals that a multimodal approach leveraging visual, mathematical, and verbal representations significantly improves critical thinking, scientific literacy, and academic performance. Furthermore, the findings highlight the pivotal role of teacher education programs in preparing educators to navigate multimodal environments. This review provides a conceptual framework for future research and curriculum development, emphasizing the need for a cohesive integration of technology and pedagogy to address the challenges of 21st-century science classrooms.